1997
DOI: 10.1073/pnas.94.14.7566
|View full text |Cite
|
Sign up to set email alerts
|

Chemical camouflage of antigenic determinants: Stealth erythrocytes

Abstract: In a number of clinical circumstances it would be desirable to artificially conceal cellular antigenic determinants to permit survival of heterologous donor cells. A case in point is the problem encountered in transfusions of patients with rare blood types or chronically transfused patients who become allosensitized to minor blood group determinants. We have tested the possibility that chemical modification of the red blood cell (RBC) membrane might serve to occlude antigenic determinants, thereby minimizing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
216
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 208 publications
(220 citation statements)
references
References 37 publications
3
216
1
Order By: Relevance
“…The control and oxidized RBC were analyzed via the microfluidic device to obtain deformability profiles. For the in vivo survival studies, murine RBC were labeled using a fluorescent, membrane anchored marker, PKH-26 (Sigma, St. Louis, MO) [45,46]. Equal numbers of control or oxidized RBC (40% hematocrit) were transfused as previously described [46,47].…”
Section: Murine Transfusion Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…The control and oxidized RBC were analyzed via the microfluidic device to obtain deformability profiles. For the in vivo survival studies, murine RBC were labeled using a fluorescent, membrane anchored marker, PKH-26 (Sigma, St. Louis, MO) [45,46]. Equal numbers of control or oxidized RBC (40% hematocrit) were transfused as previously described [46,47].…”
Section: Murine Transfusion Modelmentioning
confidence: 99%
“…For the in vivo survival studies, murine RBC were labeled using a fluorescent, membrane anchored marker, PKH-26 (Sigma, St. Louis, MO) [45,46]. Equal numbers of control or oxidized RBC (40% hematocrit) were transfused as previously described [46,47]. Blood samples from the recipient mice were followed until the labeled RBC were cleared from circulation (approximately 40-50 days for allotransfusions).…”
Section: Murine Transfusion Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that hydrophilic surfaces have decreased total protein adsorption and are also more biocompatible [12]. Thus, mPEG grafting generates a steric barrier while simultaneously biophysically camouflaging surface charge thus reducing immune recognition of implantable biomaterials, allogeneic red blood cells [5,[13][14][15][16][17][18], lymphocytes [3,4,[19][20][21] and viruses ( Figure 6BD) [22]. As shown in this study, consequent to PEGylation, latex particles demonstrated significant inhibition of protein adsorption in a polymer doseand length-dependent manner, as measured quantitatively with colorimetric protein assay and flow cytometry ( Figure 2A and B) and qualitatively by SDS-PAGE, fluorescent microscopy and iTRAQ-MS analysis (Figures 3-5).…”
Section: Discussionmentioning
confidence: 99%
“…A similar concept of immunomodulation can be applied to biological products. Immunocamouflage of cells and tissues refers to the biophysical and biological camouflage of cell surfaces from interaction with other cells, macromolecules and viruses [3][4][5][6]. This "biomaterials" approach for tissue engineering has emerged as a promising technique for preventing allorecognition of foreign cells, particularly in the context of transfusion and transplantation medicine.…”
mentioning
confidence: 99%